Parenting from a psychosocial perspective - Boukraa, Imene (Journal of Human Sciences, 2021)
The psychological, social and moral development of a child requires a set of skills that parents must use. Therefore, in this article we will make clear the importance of parenting in the child's life, as well as the nature of the practices that must be adopted by the parents at each stage of the child's development, especially as these educational practices have a strong relationship with the extent of the child's acquisition of social skills and normal growth.